Investigation of the water barrier properties of graft copolymer latex films of acrylate and poly(dimethylsiloxane) macromonomers synthesized by RAFT miniemulsion polymerization. (5th April 2022) - Jin, Linlin; Tian, Junkai; Li, Jiawei; Yan, Xiaofei; Qi, Dongming
Graphical abstract: Highlights: Waterborne acrylic-polydimethylsiloxane copolymers with high PDMS content of up to 50% were prepared via RAFT miniemulsion polymerization. The PDMS graft copolymer latex films exhibit excellent water barrier property. Different state of water in films is measured by DSC. A bicontinuous gyroid texture in bulk films provides excellent water barrier property. Abstract: It is challenging to improve the water barrier performance for waterborne protective coating. We synthesized a series of acrylic-polydimethylsiloxane (PDMS) graft copolymer latexes p(MMA -co- BA) -g- PDMS) with high PDMS content of up to 50%, which were considered as bottle-brush polymers using reversible addition-fragmentation chain transfer mediated "macromonomer" miniemulsion copolymerization. We investigated the effect of PDMS side chains on the water barrier performance of graft copolymer latex film derived from these particles and their utilization in anti-corrosion coatings. The water contact angle reaches 117° for films cast from aqueous dispersions of graft copolymers with 50% PDMS, which indicates that their surface is significantly enriched with PDMS. The increase in PDMS content has a highly positive effect on the water barrier performance. Differential scanning calorimeter (DSC) on copolymer films after soaking in water indicates that the high PDMS content (50% PDMS) graft copolymer has only freezing bound water in films. Electrochemical impedance spectra tests showed that the graft copolymer exhibited a significant improvement in corrosion resistance over the control polyacrylate sample without PDMS. Furthermore, transmission electron microscopy observations reveal that the PDMS phase changes from a spherical domain texture to a bicontinuous gyroid texture in the bulk of latex films with the increasing PDMS content, which makes them suitable as waterborne anti-corrosion silicone coatings.